EXPERIENCE OF COMPACTION OF THE BASES OF LARGE BUILDINGS AND CORES OF EARTHEN DAMS OF WATERWORKS IN SEISMIC AREAS WITH OPTIMAL HUMIDITY OF LOESS SOIL (Academia Science Repository, 2023)
In this scientific study, the issues of compaction of the foundations of large buildings built in seismic areas and the rods of underground hydraulic dams with optimal moisture content in liosimal soils were considered.The results of an experiment conducted in the field and laboratory conditions on compaction of the foundations of large buildings and walls of a waterproof screen-partition, which are erected in the central part (core) of hydraulic dams with soils, at optimal soil moisture liosimon. Recommendations are given for compacting the floors of large buildings built in earthquake-prone areas and the cores of underground hydraulic dams with vibration shocks at optimal humidity of liosim soils.